The Geneva Papers
VIII, 261 p.
Keywords: In January 1976, Raymond Barre, the first President of The Geneva Association, and Orio Giarini, its first Secretary General, founded The Geneva Papers on Risk and Insurance with the main goal of supporting and encouraging research in the economics of risk and insurance. At that time, research in the field of insurance was still embryonic and insurance was regarded as peripheral social activity. When sustained economic growth gained traction, the function of insurance gradually emerged as a key contributor to economic development. By integrating uncertainty into economic theory and benefiting from the progress of both financial economics and decision theory, research developed further in the field of insurance economics and risk management, and is now prolific. The Geneva Papers on Risk and Insurance undeniably contributed to this evolution and its impact on research in insurance has largely exceeded what its two founding members could have expected. This volume is a special collection of papers celebrating 40 Years of The Geneva Papers on Risk and Insurance. The collection looks back at the storied history of The Geneva Papers on Risk and Insurance and features papers from some of the esteemed authors who have contributed to the journal in its lifetime. This collection of papers highlights just a few of the many themes addressed in the papers published by the journal since it was created. Nevertheless, the selection exemplifies the richness and variety of topics the field of insurance covers.